PENGELOLAAN ARSIP INAKTIF DI DIREKTORAT PENGELOLAAN DATA DAN PENYAJIAN INFORMASI APARATUR SIPIL NEGARA, BADAN KEPEGAWAIAN NEGARA: - Shakira Anesia; Saifullah Zakaria; Jovanscha Qisty Adinda (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Archives play a crucial role in an institution. They serve as a means of storing, managing, and providing information and documents. The purpose of this study is to analyze the management of inactive archives within the Directorate of Data Management and Information Presentation of the State Civil Service, National Civil Service Agency. This study is a qualitative study with data collection methods through observation during internships, interviews, and library research. The results of this study indicate that the management of inactive archives within the Directorate of Data Management and Information Presentation of the State Civil Service has not been running optimally due to several obstacles that hinder the management of inactive archives. These obstacles include a lack of human resources, the presence of inactive archives that have not been resolved in previous years, resulting in a buildup of archive workloads and an archivist's workload that is not in accordance with their duties and functions. Therefore, the National Civil Service Agency (BKN) has conducted employee recruitment, but this is still insufficient to meet the existing shortage. Therefore, it is necessary to evaluate and procure human resources according to the needs of the work unit, procure supporting staff, and review the employee workload with existing human resources.